2023
DOI: 10.1021/acsnano.2c11809
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable, Solvent Response Cellulose Nanocrystal/Waterborne Polyurethane Nanocomposites with Encryption Capability

Abstract: Cellulose nanocrystal (CNC)-based chiral nematic structure is widely used in stimulus response and sensing. A popular area of research is enhancing the mechanical characteristics and environmental adaptability of chiral nematic materials. In this paper, a flexible photonic film with self-healing ability (FPFS) was prepared by combining waterborne polyurethane containing dynamic covalent disulfide bonds (SSWPU) with CNC. The results found that the FPFS showed excellent toughness under the action of stretching, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…Drawing of the encrypted package pattern and its display shape under different polarized light. Adapted with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Application Of Bspumentioning
confidence: 99%
“…Drawing of the encrypted package pattern and its display shape under different polarized light. Adapted with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Application Of Bspumentioning
confidence: 99%
“…So, at this moment, the preparation of self-healing sensors is based on the intrinsic healing system. Generally speaking, the dynamic structures required for the preparation of intrinsic healing materials include covalent structures: D−A bonds, 27 SS bonds, 28,29 or ester bonds 30 and noncovalent structures: hydrogen bonds, 31 metal−ligand networks, 32 or macromolecular diffusion systems. Studies have shown that polymers containing dynamic SS bonds can be cross-linked to form rapid healing systems, the required conditions are mild, and some systems can even heal cracks without external stimulation.…”
Section: Characterization Of Healing Propertiesmentioning
confidence: 99%
“…Disulfide bonds have attracted much attention because disulfide exchange can occur at moderate temperatures with the assistance of external stimuli. Polymers containing aliphatic disulfide bonds were reversibly broken and recombined at room temperature under sunlight, , in the presence of water, or after a relatively long healing time (48 h) . However, activation by external stimuli can lead to detrimental side effects, such as discoloring, crazing, bending, and swelling, which can impact the integrity of materials.…”
Section: Introductionmentioning
confidence: 99%